Fetal RHD Genotyping Using Real-Time Polymerase Chain Reaction Analysis of Cell-Free Fetal DNA in Pregnancy of RhD Negative Women in South of Iran - Moezzi, Leili (Int J Fertil Steril, 2016)
BACKGROUND: Maternal-fetal RhD antigen incompatibility causes approximately 50% of clinically significant alloimmunization cases. The routine use of prophylactic anti-D immunoglobulin has dramatically reduced hemolytic disease of the fetus and newborn. Recently, fetal RHD genotyping in RhD negative pregnant women has been suggested for appropriate use of anti-D immunoglobulin antenatal prophylaxis and decrease unnecessary prenatal interventions. MATERIALS AND METHODS: In this prospective cohort study, in order to develop a reliable and non-invasive method for fetal RHD genotyping, cell free fetal DNA (cffD- NA) was extracted from maternal plasma. Real-time quantitative polymerase chain reaction (qPCR) for detection of RHD exons 7, 5, 10 and intron 4 was performed and the results were compared to the serological results of cord blood cells as the gold standard method. SRY gene and hypermethylated Ras-association domain family member 1 (RASSF1A) gene were used to confirm the presence of fetal DNA in male and female fetuses, respectively. RESULTS: Out of 48 fetuses between 8 and 32 weeks (wks) of gestational age (GA), we correctly diagnosed 45 cases (93.75%) of RHD positive fetuses and 2 cases (4.16%) of the RHD negative one. Exon 7 was amplified in one sample, while three other RHD gene sequences were not detected; the sample was classified as inconclusive, and the RhD serology result after birth showed that the fetus was RhD-negative. CONCLUSION: Our results showed high accuracy of the qPCR method using cffDNA for fetal RHD genotyping and implicate on the efficiency of this technique to predict the competence of anti-D immunoglobulin administration.